Transport and killing mechanism of a novel camptothecin-deoxycholic acid derivate on hepatocellular carcinoma cells. (July 2014) - Li, Qingyong; Liu, Tianyu; Li, Yunchao; Luo, Shuyue; Zhu, Qiaochu; Zhang, Li; Zhao, Tengfei
Abstract Camptothecin-20(s)-O-glycine ester-[N-(3′α, 12′α-dihydroxy-24′-carbonyl-5′β-cholan)] (A2), 10-(3′α, 12′α-dihydroxy-5′β-cholan-24′-carboxyl)-(20 s)-camptothecin (C2), and 10-O-(3-O-(3′α, 12′α-dihydroxy-24′-carbonyl-5′β-cholan)-propyl)-(20S)-camptothecin (D2) are novel camptothecin-deoxycholic acid analogues. MTT assays were performed to assess the anticancer activity of these compounds against hepatocellular carcinoma SMMC-7721, breast carcinoma MCF-7, and colorectal carcinoma HCT-116 cells. A2 had a high killing ability on SMMC-7721 cells selectively, but C2 and D2 did not exhibit selectivity with regard to SMMC-7721 killing. Uptake assays were performed in an effort to elucidate the transport mechanisms of A2 into SMMC-7721 cells. A2 increased the mRNA expression of OATP1B3 (an organic anion-transporting polypeptide) and uptake of A2 was inhibited by rifampin (inhibitor of OATP1B3), which indicated that the transporter-mediated transport of A2 was mediated by OATP1B3. In addition, according to the western blot and apoptosis assays, we found that A2 killed SMMC-7721 cells by inducing cell apoptosis mainly via an AIF (apoptosis-inducing factor) pathway and a caspase-dependent mitochondria apoptosis pathway.